Climate variability, drought, and vegetation - a comparison of three district municipalities in Northern KwaZulu-Natal, South Africa - Fatokun, Kayode (International Journal of Innovative Research and Scientific Studies, 2025)
A study was conducted to compare climate variability, drought, and their effects on vegetation in northern KwaZulu-Natal. The assessment was done by examining the weather elements (rainfall, humidity, and temperature) over six years (2017-2022) in the three district municipalities of northern KwaZulu-Natal. The three district municipalities investigated were Zululand, King Cetshwayo, and uMkhanyakude. The spectral/drought (Rainfall Anomaly Index) and the vegetation indices [Modified Water Difference Index (MWDI) and Normalized Difference Vegetation Index (NDVI)] were also investigated. The results showed significant differences in humidity, temperature, and rainfall between the three district municipalities. There were indications that drought occurred at different times of the year in the studied municipalities. The intensity and duration of the drought also varied. Other findings include a correlation between rainfall and the vegetation indices. On average, King Cetshwayo received more rainfall than both uMkhanyakude and Zululand District Municipalities. uMkhanyakude had the least rainfall and was the most drought-prone, especially between May and September. The outcome of this study will undoubtedly contribute to how farmers in the three district municipalities decide when, what, and where to plant their crops to avoid or reduce the negative impact of climatic changes on crop growth and, consequently, on the yields of their crops.